Trypsin-mediated enzymatic degradation of type II collagen in the human vitreous - van Deemter, Mariëlle (Molecular Vision, 2013)
PURPOSE: Aging of the vitreous body can result in sight-threatening pathology. One aspect of vitreous aging is liquefaction, which results from the vanishing of collagen fibrils. We investigated the possibility that trypsins are involved in vitreous type II collagen degradation. METHODS: Immunohistochemistry and western blotting were used for detecting and locating trypsin isoforms in the vitreous and retina of human donor eyes. The capability of the retina to produce these trypsins was analyzed with polymerase chain reaction. Whether the different trypsins degraded type II collagen was tested in vitro. The sizes of the in vitro induced type II collagen degradation products were compared to those present in the vitreous of human eyes of different ages. RESULTS: Trypsin-1 and trypsin-2 were detected in the vitreous. In the retina, messenger ribonucleic acid (mRNA) coding for trypsin-2, -3, and -4 was present. Using immunohistochemistry, trypsin-2 was detected in microglial cells located in the vitreous and the retina. All trypsin isoforms degraded type II collagen and produced degradation products of similar sizes as those present in the vitreous. CONCLUSIONS: Trypsin-1 and trypsin-2 appear to have a function in the degradation of vitreous type II collagen. They could therefore have a role in the development of vitreous liquefaction.